Admission HDL-C and recurrence risk of hypertriglyceridemia-induced acute pancreatitis: a multicenter cohort study - Liu, Jianying; Xu, Haimei; Huang, Chenchen; Qiu, Xiaonan; Lu, Xuefeng; Weng, Chengzhao; Wang, Chao; Xu, Yijiao (Frontiers in Nutrition, 2026)
BackgroundHypertriglyceridemia-induced acute pancreatitis (HTG-AP) carries a high risk of post-discharge recurrence. Whether admission high-density lipoprotein cholesterol (HDL-C) independently predicts recurrence and how its effect varies over time remain unclear.MethodsA multicenter retrospective study was conducted, including consecutive HTG-AP inpatients from three hospitals from January 2020 to March 2025. The primary endpoint was overall post-discharge recurrence; while the secondary endpoints included recurrence within 6 and 12 months. HDL-C, analyzed both as a continuous variable and by tertiles, was evaluated using Cox models with progressive adjustment. Dose–response was examined by restricted cubic splines (RCS). Time-varying effects were assessed with landmark analyses (0–6 and 6–12 months) and an HDL × log(time) interaction. Robustness was tested using inverse probability of treatment weighting (IPTW). Restricted mean time free of recurrence (RMST) quantified absolute differences.ResultsA total of 440 patients were enrolled, and the median follow-up duration was 14.0 months. Lower admission HDL-C was associated with a higher recurrence risk. In the fully adjusted model, each 1 mmol/L increase in HDL-C was associated with a 77% lower hazard of overall recurrence (HR 0.23, 95% CI 0.11–0.48; p < 0.001). Compared with the lowest tertile (T1), risks were reduced in T2 (HR 0.42, 95% CI 0.27–0.64) and T3 (HR 0.33, 95% CI 0.19–0.55; p for trend<0.001). RCS showed a clear linear dose–response with risk plateauing at higher HDL-C. Landmark analyses localized the predictive value to the first year: 0–6 months HR 0.045 (95%CI: 0.012–0.171; p < 0.001) and 6–12 months HR 0.176 (95%CI: 0.054–0.568; p = 0.004); no association was observed beyond 12 months (p = 0.197). RMST within 12 months was 2.2 months shorter in T1 and 0.5 months shorter in T2 versus T3. Findings were consistent after IPTW (0–6 months aHR = 1.76, 95%CI: 1.12–2.77; 6–12 months aHR = 2.27, 95%CI: 1.38–3.73; 12-month aHR = 3.79, 95%CI: 1.92–7.48; overall aHR = 1.80, 95%CI: 1.14–2.83).ConclusionLow admission HDL-C is an independent predictor of HTG-AP recurrence with a linear risk gradient, and its predictive effect is most pronounced within 12 months after discharge. Given its stability and accessibility, HDL-C can aid early identification of high-risk patients and inform targeted follow-up and prevention strategies.